The Old Woman Who Lived in a Shoe; Or, There's No Place Like Home - Douglas, Amanda M., 1831-1916 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Old Woman Who Lived in a Shoe; Or, There's No Place Like Home" by Amanda M. Douglas is a children$1 (Bs fiction novel written in the late 19th century. This heartwarming story centers around the life and experiences of Granny Kenneth and her six orphaned grandchildren as they navigate challenges of poverty, love, and family life. The narrative unfolds in a delightful, whimsical manner, drawing inspiration from the traditional nursery rhyme about the old woman who lived in a shoe. The opening of the book introduces us to the lively household of Granny Kenneth and her grandchildren, primarily through the characters Hal, Joe, Flossy, and their younger siblings. The children engage in playful banter, daydream about adventures, and reflect on their struggles as orphans. Joe, in particular, declares a humorous realization that they resemble the children from the nursery rhyme, leading to a lighthearted exploration of their life in a dilapidated house they refer to as a 'shoe.' As they prepare for their grandmother$1 (Bs return from work, the children's distinct personalities emerge, illustrating both the joys and hardships they face together, setting the stage for a story rich in themes of resilience and familial love. (This is an automatically generated summary.)s
Release date is 2013-09-06
E-text prepared by Melissa McDaniel, Sue Fleming, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Christian life -- Juvenile fiction; Conduct of life -- Juvenile fiction; Children -- Conduct of life -- Juvenile fiction; Christmas -- Juvenile fiction; Mutiny -- Juvenile fiction; Fortune -- Juvenile fiction; Fourth of July -- Juvenile fiction